(untitled) (Asian Journal of Current Engineering and Maths, 2013)
In this paper, we have obtained existence, uniqueness and error estimate concerning deficient discrete quartic spline interpolant which matching to given functional values at intermediate points between successive mesh points and difference at boundary points.